Розробка платформи для управління та пошуку онлайн курсів - Гринишина, С. О. (ХНУРЕ, 2024)
This article explores the increasing popularity and accessibility of online education in today's digital era. It highlights the growing demand for convenient platforms to search, select, and manage online courses, emphasizing the need for effective solutions. The thesis aims to address this by developing a user-friendly platform for managing and searching online courses. Leveraging the Angular framework, the platform will offer modular architecture and a component-based approach for enhanced functionality. Through a comprehensive review of diverse sources, including scientific articles and official documentation, the article underscores the significance of user-centric design and meticulous development to create a seamless online learning experience.
Keywords: онлайн курси; пошук онлайн курсів